Biochanin A partially restores the activity of ofloxacin and ciprofloxacin against topoisomerase IV mutation‐associated fluoroquinolone‐resistantUreaplasmaspecies. Issue 11 (November 2017) - Jin, Hong; Qi, Chao; Zou, Yanping; Kong, Yingying; Ruan, Zhi; Ding, Honghui; Xie, Xinyou; Zhang, Jun
Abstract : Purpose. : This study aims to investigate the synergistic antimicrobial activity of four phytoalexins in combination with fluoroquinolones against Ureaplasma spp., a genus of cell wall‐free bacteria that are intrinsically resistant to many available antibiotics, making treatment inherently difficult. Methodology. : A total of 22958 urogenital tract specimens were assessed for Ureaplasma spp. identification and antimicrobial susceptibility. From these, 31 epidemiologically unrelated strains were randomly selected for antimicrobial susceptibility testing to determine the minimum inhibitory concentration (MIC) of four fluoroquinolones and the corresponding quinolone resistance‐determining regions (QRDRs). Synergistic effects between fluoroquinolones and four phytoalexins (reserpine, piperine, carvacrol and biochanin A) were evaluated by fractional inhibitory concentration indices (FICIs). Results. : Analysis of the QRDRs suggested a vital role for the mutation of Ser‐83→Leu in ParC in fluoroquinolone‐resistant strains, and the occurrence of mutations in QRDRs showed significant associations with the breakpoint of levofloxacin. Moreover, diverse synergistic effects of the four phytoalexins with ofloxacin or ciprofloxacin were observed and biochanin A was able to enhance the antimicrobial activity of fluoroquinolones significantly. Conclusion. : This is the first report of the antimicrobial activity of biochanin A in combination with fluoroquinolones against a pathogenic mycoplasma, and opens up the possibility of using components of biochanin A as a promising therapeutic option for treating antibiotic‐resistant Ureaplasma spp. infections.